Comparison of two different cooling systems in alleviating thermal and physiological strain during prolonged exercise in the heat - Keller, S.; Kohne, S.; Bloch, W.; Schumann, M. (Ergonomics, 2021)
This study compared the efficacy of an ice vest comprising of water (WATER) or a water-carbon (CARBON) emulsion on thermophysiological responses to strenuous exercise in the heat. Twelve male cyclists completed three 50-minute constant workload trials (55% of peak power output, ambient temperature 30.4 ± 0.6 °C) with WATER, CARBON and without ice vest (CONTROL), respectively. The increase in core body temperature (Tcore) was lower in WATER at 40 (-0.49 ± 0.34 °C) and 50 minutes (-0.48 ± 0.48 °C) and in CARBON at 30 (-0.41 ± 0.48 °C), 40 (-0.54 ± 0.51 °C), and 50 minutes (-0.67 ± 0.62 °C) as compared to CONTROL (P < 0.05, ES >0.8). While heart rate and blood lactate kinetics did not differ between the conditions, statistical main effects in favor of both WATER and CARBON were found for thermal sensation (condition P < 0.001 and interaction P < 0.01) and rating of perceived exertion (condition P < 0.05). Per-cooling with CARBON and WATER similarly reduced Tcore but not physiological strain during prolonged exercise in the heat.